Glycerol to Glyceraldehyde Oxidation Reaction Over Pt-Based Catalysts Under Base-Free Conditions - El Roz, Ayman; Fongarland, Pascal; Dumeignil, Franck; Capron, Mickael (Frontiers in Chemistry, 2019)
Glycerol valorization through partial oxidation is a good way for obtaining many different molecules with high added value such as glyceric acid, tartronic acid, dihydroxyacetone, etc. Among the potential products, glyceraldehyde is an interesting chemical compound for its various applications in different domains such as organic chemistry, medical and cosmetic industries. In the present paper, we studied the effect of different supports on the glycerol oxidation reaction in a batch reactor applying base-free conditions. The tested catalysts were Pt-based materials deposited on various supports (i.e., SiO2, TiO2, ZSM-5, -Al2O3), which were synthesized using a deposition method followed by a chemical reduction. The catalysts were extensively characterized (BET, ICP, XRD, TEM, XPS) highlighting differences in terms of specific surface areas, textural properties and Pt nanoparticles sizes. We evidenced a direct relation between glycerol conversion and glyceraldehyde selectivity (i.e., increase glycerol conversion leads to a decrease in glyceraldehyde selectivity). The Pt/-Al2O3 catalysts exhibited the highest activity, but their selectivity to glyceraldehyde significantly decreased with time on stream. Pt/SiO2 presented the highest selectivity to glyceraldehyde owing to a slower reaction rate, which allows envisioning technical opportunities to continuously extract the formed glyceraldehyde from the mixture.